FPGA Digital Architecture for Multilevel Synchronous Optimal PulseWidth ModulationWith Seamless Pulse Pattern Transitions - Lago, Jackson; Steckling, Lúcio; Heldwein, Marcelo Lobo (Eletrônica de Potência, 2023)
received the B.S. degrees in electrical engineering from the University Center of Jaraguá do Sul (UNERJ), Jaraguá do Sul, Brazil, in 2009, and the M.S. and Ph.D degrees in electrical engineering from the Federal University of Santa Catarina (UFSC), Florianopólis, Brazil, in 2011 and 2015, respectively. From 2015 to 2016 he was a researcher at the Power Electronics Institute (INEP) of the Federal University of Santa Catarina (UFSC). He is currently a Professor with the Electrotechnical Department at the Federal Institute of Education, Science and Technology of Santa Catarina (IFSC). His research interests include power electronics and electrical machines drives. He is a member of the Brazilian Power Electronic Society (SOBRAEP).